مفهوم النقد الإبداعي: Creative Criticism Concept - Abdulilah Alkhani, Rima (SIBAWAYH Arabic Language and Education, 2020)
The first rule of good style is that the author has what is said as a critical identity. This is what Schopenhauer says about every good writer, far from unimportant writing, so having what is said is a difficult challenge, if it does not reach the impossibility. And I say here: Since there is no text without errors at all, nor is there any complete criticism, but it is jurisprudence from a single point of view, has experience that makes it offer everything important, then there is a first criticism and a second criticism and a third criticism. As a careful look at the level of critical experience, what is it? It is what we are talking about in this research.